2018
DOI: 10.1111/add.14279
|View full text |Cite
|
Sign up to set email alerts
|

Is there gender convergence in risky drinking when taking birth cohorts into account? Evidence from an Australian national survey 2001–13

Abstract: In Australia, gender convergence in risky drinking since 2001 has been evident only in people aged 50-69 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
(33 reference statements)
2
31
0
1
Order By: Relevance
“…Men have historically consumed markedly more alcohol than women in Australia and there has been little narrowing of this gap in recent years. 15 Similarly, higher rates of drinking outside the major cities have been well established. 16 Somewhat surprisingly, and in contrast to some studies that looked at more inclusive measures of 'risky drinking' , there were few other strong relationships with sociodemographic factors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Men have historically consumed markedly more alcohol than women in Australia and there has been little narrowing of this gap in recent years. 15 Similarly, higher rates of drinking outside the major cities have been well established. 16 Somewhat surprisingly, and in contrast to some studies that looked at more inclusive measures of 'risky drinking' , there were few other strong relationships with sociodemographic factors.…”
Section: Discussionmentioning
confidence: 97%
“…Men and people from regional and rural areas were more likely to be among the heaviest drinkers. Men have historically consumed markedly more alcohol than women in Australia and there has been little narrowing of this gap in recent years 15 . Similarly, higher rates of drinking outside the major cities have been well established 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used data from the National Drug Strategy Household Survey (NDSHS), the largest nationally representative household survey in Australia, to: Estimate the prevalence of non‐medical use of pharmaceutical opioids in the Australian population in two types of opioid users—those who predominantly use opioids only and those who use opioid in addition to other illicit substances, because some studies suggest that these two groups are substantially different . Examine the socio‐demographic (such as gender, age, employment status, etc.—see Method section), psychological, health, and behavioural correlates (such as smoking status and alcohol risk) of these two types of opioid user. These variables are selected because they have been found to be associated with other substance use, such as alcohol , tobacco , cannabis , amphetamine and polysubstance use in the Australian population. …”
Section: Introductionmentioning
confidence: 99%
“…Examine the socio-demographic (such as gender, age, employment status, etc.-see Method section), psychological, health, and behavioural correlates (such as smoking status and alcohol risk) of these two types of opioid user. These variables are selected because they have been found to be associated with other substance use, such as alcohol [14,15], tobacco [16,17], cannabis [18], amphetamine [19] and polysubstance use [20][21][22] in the Australian population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attempts to clarify the nature of the narrowing gender gap have identified a cohort effect among Australian survey respondents. Age‐specific analyses of Australian National Drug Strategy Household Survey data from 2001 to 2013 found that gender convergence in risky drinking was only observed for 50–69 year olds (Livingston, Callinan, Dietze, Stanesby, & Kuntsche, ). Coupled with results from the 2016 Australian National Drug Strategy Household Survey, drinking in excess of the lifetime risk guideline continued to increase for 50–59 year olds, and women aged 30–39 years had a significant increase in single‐occasion risky drinking (Claydon et al, ).…”
Section: Introductionmentioning
confidence: 99%